2023
DOI: 10.3390/s24010035
|View full text |Cite
|
Sign up to set email alerts
|

Basin Scale Soil Moisture Estimation with Grid SWAT and LESTKF Based on WSN

Ying Zhang,
Jinliang Hou,
Chunlin Huang

Abstract: This research utilized in situ soil moisture observations in a coupled grid Soil and Water Assessment Tool (SWAT) and Parallel Data Assimilation Framework (PDAF) data assimilation system, resulting in significant enhancements in soil moisture estimation. By incorporating Wireless Sensor Network (WSN) data (WATERNET), the method captured and integrated local soil moisture characteristics, thereby improving regional model state estimations. The use of varying observation search radii with the Local Error-subspac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 87 publications
0
2
0
Order By: Relevance
“…A wireless sensor network (WSN) is an approach to collect data for extended and remote areas. Zhang et al [ 27 ] claimed that in situ soil moisture observation can be reported in a radius exceeding 20 km. This is mainly dependent on careful selection of the required range.…”
Section: Related Studiesmentioning
confidence: 99%
“…A wireless sensor network (WSN) is an approach to collect data for extended and remote areas. Zhang et al [ 27 ] claimed that in situ soil moisture observation can be reported in a radius exceeding 20 km. This is mainly dependent on careful selection of the required range.…”
Section: Related Studiesmentioning
confidence: 99%
“…Researchers have prepared a series of new nanoenzymes based on MOFs, which show excellent enzyme-like activities and good prospects for application (Natalini et al, 2021;Ni et al, 2021;Zhang et al, 2023). Wang et al synthesized a Cu-MOF with peroxidase-like activity using Cu 2+ and 4,4 ′ -bipyridine using a coordinated induction strategy (Chen et al, 2020).…”
mentioning
confidence: 99%